Perancangan UI UX Sistem Reservasi Lapangan Padel dengan Rule Based Dynamic Pricing Menggunakan SUS - Afina Rahmani; Muhammad Nursalman; Ani Anisyah (ITB Ahmad Dahlan Jakarta, 2026)
The development of digital technology has increased the use of web-based reservation systems in various sectors, including sports. However, several problems still exist, such as unclear scheduling information, lack of price transparency, and inefficient booking processes that are difficult for users to understand. This study aims to design and evaluate a UI/UX prototype of a padel court reservation system with rule-based dynamic pricing to improve user experience. The method used is Research and Development (R&D), consisting of needs analysis, design using Figma, and usability testing using the System Usability Scale (SUS). The testing involved 39 respondents who had interacted with the system prototype. The results show that the average SUS score is 78.59, which falls into the good and acceptable category. This indicates that the designed system has good usability and provides ease of use in the reservation process. Therefore, the developed prototype can be an alternative solution to improve the quality of digital sports reservation systems.